Minor second intervals: A shared signature for infant cries and sadness in music. (March 2022) - Zeloni, Gabriele; Pavani, Francesco
In Western music and in music of other cultures, minor chords, modes and intervals evoke sadness. It has been proposed that this emotional interpretation of melodic intervals (the distance between two pitches, expressed in semitones) is common to music and vocal expressions. Here, we asked expert musicians to transcribe into music scores spontaneous vocalizations of pre-verbal infants to test the hypothesis that melodic intervals that evoke sadness in music (i.e., minor 2nd) are more represented in cry compared to neutral utterances. Results showed that the unison, major 2nd, minor 2nd, major 3rd, minor 3rd, perfect 4th and perfect 5th are all represented in infant vocalizations. However, minor 2nd outnumbered all other intervals in cry vocalizations, but not in neutral babbling. These findings suggest that the association between minor intervals and sadness may develop in humans because a critically relevant social cue (infant cry) contains a statistical regularity: the association between minor 2nd and negative emotional valence.